Blurring the boundaries between networking and IT security. Issue 1 (January 2018) - Nicholson, Dave
Abstract : Networking and security used to be largely separate IT methodologies. They were even built separately. Traditionally, networks were constructed on standard building blocks (switches, routers etc) and security solutions such as perimeter firewalls, intrusion prevention systems and the like were applied afterwards. Networking and security used to be largely separate IT methodologies. As such, they could be treated as separate domains of the business. That's not the case today. There is now a huge overlap between the two areas. It is becoming common to think about the network itself as a security enforcement platform and these two elements of modern technology systems are becoming inextricably entwined. This development will be overwhelmingly positive both for solutions providers and their end customers, says Dave Nicholson of Axial Systems.